FPGA-based power meter implementation for three-phase three-wire and four-wire power systems, according to IEEE 1459-2010 standard - De Oro Arenas, Luis [UNESP] (2018)
This paper proposes an electric power measurement implementation by using an FPGA (Field Programmable Gate Arrays) device, based on the power calculation theory defined by the IEEE 1459-2010 Standard. The modules synthesized in the programmable logic device (PLD) are fully developed in a hardware description language (HDL), allowing the control over all variables and signals present in the system. This methodology attends the windowing specifications established by the NBR IEC 61000-4-30:2011 Standard for power quality measurement methods. Finally, the hardware structure described in the FPGA and the developed analog signal conditioning platform are presented along with experimental results for three-phase power systems in several scenarios.